Natural Polymers and Cosmeceuticals for a Healthy and Circular Life: The Examples of Chitin, Chitosan, and Lignin - Pierfrancesco Morganti; Gianluca Morganti; Maria-Beatrice Coltelli (Cosmetics, 2023)
The present review considers the design and introduction of new cosmeceuticals in the market, based on natural polymers and active molecules extracted from biomass, in a biomimetic strategy, starting with a consideration of the biochemical mechanisms, followed by natural precision biopolymer production. After introducing the contest of nanobiotechnology in relationship with its applicability for skin contact products and classifying the currently available sustainable polymers, some widely selected abundant biopolymers (chitin, chitosan, and lignin), showing specific functionalities (anti-microbial, anti-oxidant, anti-inflammatory, etc.), are described, especially considering the possibility to combine them in nanostructured tissues, powders, and coatings for producing new cosmeceuticals, but with potentialities in other sectors, such as biomedical, personal care, and packaging sectors. After observing the general increase in market wellness and beauty forecasts over the next few years, parallelisms between nano and macro scales have suggested that nanobiotechnology application expresses the necessity to follow a better way of producing, selecting, and consuming goods that will help to transform the actual linear economy in a circular economy, based on redesigning, reducing, recycling, and reusing.